Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1999)
Table of Content We Go Round and Round in the Night and Are Consumed by Fire – Cerith Wyn Evans by Greg Hilty Ellsworth Kelly An American in Paris by Thomas Kellein To Hell with Pictures – Elsworth Kelly’s Walls by Briony Fer Forever in the Present by Simone Maurer Why Kelly Now? by David Rimanelli Vanessa Beecroft US Navy SEALs by Russel Ferguson Parades by Pier Luigi Tazzi Clasic Cruelty by Keith Seward Let the Picture Do the Talking by Ian Avgikos Jorge Pardo What Is Lost for Arts Is Gained for Life by Russell Ferguson The Tonality of Contradictory Settings by Christina Végh Off the Table by Camiel van Winkel Raise High the Roof Beam, Carpenters, Jorge Pardo and the Human Scale by Frank Frangenberg 4166 Sea View Lane by Kate Bush Christian Markley – Indexicality Concrète by Thomas Y. Levine On Location – Diana Thater by Lynne Cooke Civilization on Its Discontents, Architectural Dialogue One, Les Infos du Paradis by Diane Lewis Art Rules, Cumulus from America by Adrian Dannatt Prag 2000, Cumulus from Europa by Petr Nedoma
Twice in the present issue readers enjoy an inside view of the New York Guggenheim. The one picture shows Ellsworth Kelly’s 1997 retrospective, mentioned with enthusiastic acclaim more than once in the articles that follow, while the other presents Vanessa Beecroft’s tableau vivant of young semi-clothed and nude women in her SHOW of 1998 at the same venue. Modernism as a lifestyle: contradiction or logical consequence? Jorge Pardo shows great determination in confronting us with this issue. One of his works is titled 4166 SEA VIEW LANE, the address of his own house in Los Angeles, which he built together with an architect. Last fall he „detoured“ visitors of the MOCA to his home, which made Kate Bush wonder whether it was „a public sculpture, a piece of architecture, a DIY house, a case study, a satellite exhibition space, a museum commission, or Jorge Pardo’s home?“ . (editorial by publisher)
boek
Keywords: Beecroft, Vanessa; Pardo, Jorge; Kelly, Ellsworth